Improved stability and efficiency of perovskite solar cells with submicron flexible barrier films deposited in air. Issue 44 (3rd November 2017) - Rolston, Nicholas; Printz, Adam D.; Hilt, Florian; Hovish, Michael Q.; Brüning, Karsten; Tassone, Christopher J.; Dauskardt, Reinhold H.
Abstract : We report on submicron organosilicate barrier films produced rapidly in air by a scalable spray plasma process that improves both the stability and efficiency of perovskite solar cells. Abstract : We report on submicron organosilicate barrier films produced rapidly in air by a scalable spray plasma process that improves both the stability and efficiency of perovskite solar cells. The plasma is at sufficiently low temperature to prevent damage to the underlying layers. Oxidizing species and heat from the plasma improve device performance by enhancing both interfacial contact and the conductivity of the hole transporting layer. The thickness of the barrier films is tunable and transparent over the entire visible spectrum. The morphology and density of the barrier are shown to improve with the addition of a fluorine-based precursor. Devices with submicron coatings exhibited significant improvements in stability, maintaining 92% of their initial power conversion efficiencies after more than 3000 h in dry heat (85 °C, 25% RH) while also being resistant to degradation under simulated operational conditions of continuous exposure to light, heat, and moisture. X-ray diffraction measurements performed while heating showed the barrier film dramatically slows the formation of PbI2 . The barrier films also are compatible with flexible devices, exhibiting no signs of cracking or delamination after 10 000 bending cycles on a 127 μm substrate with a bending radius of 1 cm.